Measurement of tritium concentration in Tigris River water samples using a flash liquid counter (Journal of the College of Basic Education, 2022)
The study aims to determine the concentration of tritium in samples from the waters of the Tigris River, for the purpose of preparing these models for measurement using the LSC liquid scintillation counter technique, as they are chemically treated by adding sodium hydroxide and potassium permanganate to obtain a pH = 11, and the results showed that the concentration of tritium in all samples The water taken from the Tigris River was within the permissible limits, which is less than (740 Bq/L) and according to the regulations of the International Atomic Energy Agency.